Vascular endothelial growth factor as a potential biomarker in systemic sclerosis: a systematic review and meta-analysis - Angelo Zinellu; Arduino A. Mangoni; Arduino A. Mangoni (Frontiers in Immunology)
IntroductionSystemic sclerosis (SSc), a chronic autoimmune condition, is characterized by microvascular dysfunction, ineffective angiogenesis, and fibrosis. The identification of robust biomarkers reflecting these processes may assist in clinical management and lead to the discovery of new therapies. We sought to address this issue by conducting a systematic review and meta-analysis of studies investigating one such biomarker, vascular endothelial growth factor (VEGF), in SSc patients and healthy controls and in SSc patients with localized or diffuse disease, different video capillaroscopy patterns (early, active, or late), and presence or absence of complications.MethodsWe searched PubMed, Scopus, and Web of Science from inception to 15 May 2024. We assessed the risk of bias and the certainty of evidence using the JBI checklist for analytical studies and GRADE, respectively.ResultsIn 42 eligible studies, compared to controls, patients with SSc had significantly higher plasma or serum VEGF concentrations (standard mean difference, SMD=0.93, 95% CI 0.71 to 1.15, p<0.001; moderate certainty). In further analyses, VEGF concentrations were significantly higher in SSc patients with diffused disease than those with localized disease (SMD=0.30, 95% CI 0.01 to 0.59, p=0.046; very low certainty), in patients with late vs. active video capillaroscopy pattern (SMD=0.35, 95% CI 0.09 to 0.61, p=0.008; very low certainty), and in patients with pulmonary hypertension than those without (SMD=0.93, 95% CI 0.34 to 1.53, p=0.002; very low certainty). By contrast, no significant differences were observed between SSc patients with and without digital ulcers, interstitial lung disease, and telangiectasias, whereas limited evidence was available for alveolitis. Meta-regression and subgroup analysis of studies investigating VEGF in SSc patients and controls showed no significant associations between the effects size and various patient and study characteristics, including SSc duration and use of corticosteroids, immunosuppressors and vasodilators. By contrast, significant associations were observed with the geographical location where the study was conducted.DiscussionThe results of this systematic review and meta-analysis suggest that VEGF can be useful in the assessment and management of SSc and in the identification of novel therapeutic strategies in this patient group.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero, identifier CRD42024552925.